1998
DOI: 10.1093/molehr/4.2.127
|View full text |Cite
|
Sign up to set email alerts
|

In-situ competition between protamine and fluorochromes for sperm DNA

Abstract: In this study we investigated the relationship between the presence of bound protamine on mouse and human sperm DNA and the level of chromomycin A3 (CMA3) and 4'6-diamidino-2-phenylindole (DAPI) fluorescence. This was accomplished by performing a competition assay between salmon protamine and fluorochromes on decondensed spermatozoa that had their nuclear proteins extracted and were fixed on slides. Various concentrations (0, 0.005, 0.0225, 0.05, 0.225, 0.5 and 5 mg/ml) of salmon protamine were added to either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 46 publications
1
24
0
2
Order By: Relevance
“…The CMA3 assay is becoming more extensively used for evaluating sperm quality as part of male fertility assessment (52,53). It provides an indirect measure of assessing protamines in sperm (54,55), where CMA3 competes with protamines for chromatin binding (47,56).…”
Section: Zubkova Effect Of Age On Spermatozoal Chromatin Fertil Stementioning
confidence: 99%
“…The CMA3 assay is becoming more extensively used for evaluating sperm quality as part of male fertility assessment (52,53). It provides an indirect measure of assessing protamines in sperm (54,55), where CMA3 competes with protamines for chromatin binding (47,56).…”
Section: Zubkova Effect Of Age On Spermatozoal Chromatin Fertil Stementioning
confidence: 99%
“…CMA 3 is a useful tool for rapid screening of subfertility in man, as it seems to allow an indirect visualization of protamine-deficient DNA (14,15,22,23). This molecule has been shown to bind as a Mg 2+ -coordinated dimer at the minor groove of GC-rich DNAs and to induce a conformational perturbation in the double helix resulting in a wider and shallower minor groove at its binding site (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons the conformational arrangement adopted by the DNA-protamine complex can limit the access of CMA 3 to the minor groove. So CMA 3 can also be used as an indicator of underprotaminated spermatozoa (23).…”
Section: Introductionmentioning
confidence: 99%
“…Major chromatin restructuring occurs in elongating and condensing spermatids, which are in turn replaced by protamines (PRMs) [12][13][14][15]. TNPs are arginine-and lysine-rich basic proteins that strongly bind to DNA, and are expressed exclusively in postmeiotic haploid spermatids.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, TNPs are phosphorylated by sperm-specific protein kinase A, and this phosphorylation/dephosphorylation cycle has been found to play an important role in the chromatin condensation process [9][10][11]. TNPs are removed from condensing chromatin and replaced by PRMs [13], which constitute the major nuclear proteins of condensed spermatids and mature spermatozoa [12,[14][15][16]. Miyagawa et al demonstrated single-nucleotide polymorphisms (SNPs) and specific variability in the TNP genes of sterile male patients [1].…”
Section: Introductionmentioning
confidence: 99%